A band-tunable strontium titanium oxysulfide catalyst and a preparation method and application thereof
By regulating the band structure of the sulfur-oxygen-titanium-strontium catalyst, the problem of low solar-to-hydrogen conversion efficiency of existing photocatalysts was solved, achieving efficient solar light absorption and improved catalytic performance.
Patent Information
- Application Number
- CN202310888149.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The low solar-to-hydrogen conversion efficiency of existing photocatalysts is mainly due to the wide band gap of strontium titanate, which leads to insufficient utilization of sunlight.
A bandgap tunable sulfur-oxygen-titanium strontium catalyst was prepared by hydrothermal method. By adjusting the ratio of sulfur to oxygen, the band structure of the catalyst was changed, forming a direct bandgap semiconductor and improving light utilization.
It improves the light utilization rate and the redox capacity of electrons and holes in the catalyst, thus extending the catalyst's lifespan.
Smart Images

Figure CN116924463B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials preparation and catalysis technology, specifically relating to a band-tunable sulfur-oxygen-titanium strontium catalyst, its preparation method, and its application. Background Technology
[0002] The energy crisis is a major global challenge, and solar energy, as the most promising clean energy source, has made solar energy conversion and storage technologies a hot research topic. Photocatalysts that absorb solar energy to electrolyze water and produce hydrogen and oxygen are a key research direction in solar energy storage. However, the solar-to-hydrogen (STH) conversion efficiency of existing photocatalysts is generally less than 1%, making the development of highly efficient photocatalysts for electrolyzing water an urgent problem to be solved.
[0003] As is well known, strontium titanate, as a typical perovskite semiconductor, has good physical and chemical stability. The main reason for the low STH efficiency of SrTiO3 is its wide band gap (Eg≈3.2eV), which means it can only absorb ultraviolet light with wavelengths below 387nm, and its utilization rate of sunlight is only 5%. Summary of the Invention
[0004] In order to overcome the shortcomings of the existing technology, the present invention aims to provide a band-tunable sulfur-oxygen-titanium-strontium catalyst, its preparation method and application, which is simple to operate, safe and pollution-free, and can improve the activity of the catalyst simultaneously without changing the stability of the catalyst.
[0005] This invention is achieved through the following technical solution:
[0006] This invention discloses a method for preparing a bandgap tunable sulfur-oxygen-titanium strontium catalyst, comprising the following steps:
[0007] Step 1: After dissolving the strontium source and titanium source, add them to an alkaline solution, stir thoroughly, and carry out a hydrothermal reaction. After centrifugation and drying, the precursor is obtained.
[0008] Step 2: Mix the precursor obtained in Step 1 with a sulfur source and calcine it at high temperature under negative pressure to obtain a bandgap tunable sulfur-oxygen-titanium-strontium catalyst.
[0009] Preferably, in step 1, the strontium source is strontium chloride or strontium hydroxide, the titanium source is tetrabutyl titanate or titanium isopropoxide, and the molar ratio of strontium to titanium is 1:1.
[0010] More preferably, the strontium source is dissolved in deionized water, and the titanium source is dissolved in anhydrous ethanol.
[0011] Preferably, in step 1, the hydrothermal reaction temperature is 80–200°C and the time is 10–30 h.
[0012] Preferably, in step 2, the sulfur source is carbon disulfide that has undergone low-temperature pretreatment at a temperature below -10°C.
[0013] Preferably, in step 2, the calcination temperature is 500–1500°C, and the calcination time is 1–8 hours.
[0014] Preferably, in step 2, the molar ratio of the precursor powder to the sulfur source is 1:8 to 20.
[0015] Preferably, the hydrothermal reaction in step 1 is carried out in a high-pressure reactor, and the calcination in step 2 is carried out in a tubular furnace.
[0016] The present invention also discloses a bandgap tunable strontium-sulfur-oxygen-titanium catalyst prepared by the above preparation method, with a morphology between nanocube and lamellar.
[0017] This invention also discloses the application of the above-mentioned band-tunable sulfur-oxygen-titanium-strontium catalyst as a photocatalyst for total water splitting.
[0018] Compared with the prior art, the present invention has the following beneficial technical effects:
[0019] The present invention relates to a band-tunable sulfur-oxygen-titanium strontium SrTi(O) x S 1-x 3. Catalyst preparation method: A hydrothermal method is used to prepare the precursor, which is mild, simple to operate, and safe. Under negative pressure, the sulfur source can rapidly volatilize into gas and fill the calcination vessel, providing a sulfur atmosphere for subsequent calcination and avoiding gas waste and toxic gas emissions caused by introducing sulfur-containing gas during high-temperature calcination. By controlling the ratio of precursor powder to sulfur source, stable catalysts with different sulfur and oxygen ratios can be obtained. Finally, the incorporation of sulfur can effectively control the band gap of the catalyst, improving its stability and water-splitting ability. SrTiO3 is an indirect band gap semiconductor; when S... 2- Replace part of O 2- This process can cause lattice distortion, leading to changes in the band structure and the formation of SrTi(O) x S 1-x SrTi(O)3 will gradually transform into a direct bandgap semiconductor, thereby improving light utilization. Therefore, by modifying SrTi(O)3... x S 1-x By precisely controlling the band structure of )3, the absorption and utilization rate of sunlight is improved, while ensuring the redox capacity of electrons and holes is maintained.
[0020] Furthermore, using strontium chloride or strontium hydroxide as strontium salts can form stable substances at lower temperatures; using tetrabutyl titanate or titanium isopropoxide as titanium sources, they are easily hydrolyzed at lower temperatures and react with strontium chloride or strontium hydroxide.
[0021] Furthermore, the hydrothermal reaction temperature is 80–200℃ and the time is 10–30h. If the temperature is below 80℃ and the time is less than 10h, the reaction is slow and incomplete; while if the temperature is above 200℃ and the time is greater than 30h, the resulting catalyst particles are too large and the energy consumption increases.
[0022] Furthermore, the sulfur source is carbon disulfide that has undergone low-temperature pretreatment, and the pretreatment temperature is below -10℃. If the temperature is too high, the carbon disulfide will volatilize too quickly, and the reaction will be incomplete.
[0023] Furthermore, calcination at a temperature of 500–1500℃ and a calcination time of 1–8h can make the crystal form of the product prepared by the reaction more stable. If the temperature is below 500℃ and the time is less than 1h, the reaction cannot proceed; if the temperature is above 1200℃ and the time is greater than 8h, the sample cannot be collected and the yield is too low.
[0024] Furthermore, the molar ratio of precursor powder to sulfur source is 1:8 to 20. If the ratio is greater than 1:8, the sulfur atmosphere in the tubular furnace will be insufficient, and the sulfidation of the precursor will not be completed. If the ratio is less than 1:20, there will be too much sulfur atmosphere in the tubular furnace, and the excessive gas pressure inside the tube will pose a risk of furnace explosion.
[0025] The present invention discloses a bandgap-tunable sulfur-oxygen-titanium-strontium catalyst prepared by the above preparation method. The internal atomic interaction of the catalyst allows the bandgap of the catalyst to be tuned by controlling the sulfur doping ratio, thereby improving the catalyst's catalytic performance.
[0026] The application of the bandgap-tunable sulfur-oxygen-titanium-strontium catalyst disclosed in this invention as a heterogeneous catalyst support, based on the different proportions of sulfur and oxygen, affects the morphology and structure of the catalyst. Its unique structure enables the catalyst itself to have a strong catalytic effect. The performance of the catalyst can be changed by regulating the band gap width through the presence of sulfur, while the stability of the catalyst can be controlled by the presence of oxygen, thus extending the catalyst lifetime. Attached Figure Description
[0027] Figure 1 The XRD pattern of the sulfur-oxygen-titanium strontium catalyst prepared in this invention is shown.
[0028] Figure 2 XRD patterns of strontium titanate, strontium titanium sulfide, and strontium sulfide titanium sulfide prepared in this invention.
[0029] Figure 3 SEM images of strontium titanate, strontium titanium sulfide, and the strontium sulfide titanium sulfide prepared in this invention. Detailed Implementation
[0030] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. These descriptions are intended to explain the invention and not to limit it.
[0031] Example 1
[0032] At room temperature, 3.16 g of strontium chloride was weighed and dissolved in deionized water, and 6.8 mL of tetrabutyl titanate was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 80 °C for hydrothermal reaction for 30 h. The precursor was obtained by centrifugation and drying.
[0033] Weigh 0.3 g of the precursor and 0.8 mL of carbon disulfide and place them in a tube furnace. Evacuate the tube furnace to negative pressure and calcine at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0034] Example 2
[0035] At room temperature, 3.14 g of strontium hydroxide was weighed and dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 80 °C for hydrothermal reaction for 30 h. The precursor was obtained by centrifugation and drying.
[0036] Weigh 0.3 g of the precursor and 0.8 mL of carbon disulfide and place them in a tube furnace. Evacuate the tube furnace to negative pressure and calcine at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0037] Example 3
[0038] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0039] Weigh 0.3 g of the precursor and 0.8 mL of carbon disulfide and place them in a tube furnace. Evacuate the tube furnace to negative pressure and calcine at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0040] Example 4
[0041] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 200 °C for a hydrothermal reaction for 10 h. The precursor was obtained by centrifugation and drying.
[0042] Weigh 0.3 g of the precursor and 0.8 mL of carbon disulfide and place them in a tube furnace. Evacuate the tube furnace to negative pressure and calcine at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0043] Example 5
[0044] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0045] 0.3 g of the precursor and 1.2 mL of carbon disulfide were weighed and placed in a tube furnace. The tube furnace was evacuated to negative pressure and calcined at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0046] Example 6
[0047] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0048] 0.3 g of the precursor and 1.6 mL of carbon disulfide were weighed and placed in a tube furnace. The tube furnace was evacuated to negative pressure and calcined at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0049] Example 7
[0050] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0051] 0.3 g of the precursor and 2.0 mL of carbon disulfide were weighed and placed in a tube furnace. The tube furnace was evacuated to negative pressure and calcined at 500 °C for 8 h to obtain SrTi(O) x S 1-x 3.
[0052] Example 8
[0053] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0054] 0.3 g of the precursor and 1.6 mL of carbon disulfide were weighed and placed in a tube furnace. The tube furnace was evacuated to negative pressure and calcined at 700 °C for 6 h to obtain SrTi(O) x S 1-x 3.
[0055] Example 9
[0056] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0057] Weigh 0.3 g of the precursor and 1.5 mL of carbon disulfide and place them in a tube furnace. Evacuate the tube furnace to negative pressure and calcine at 1000 °C for 4 h to obtain SrTi(O) x S 1-x 3.
[0058] Example 10
[0059] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0060] 0.3 g of the precursor and 1.5 mL of carbon disulfide were weighed and placed in a tube furnace. The tube furnace was evacuated to negative pressure and calcined at 1200 °C for 2 h to obtain SrTi(O) x S 1-x 3.
[0061] Example 11
[0062] At room temperature, 3.14 g of strontium hydroxide was dissolved in deionized water, and 5.7 mL of titanium isopropoxide was dissolved in anhydrous ethanol. Sodium hydroxide solution was added, and the mixture was thoroughly mixed. The mixture was then placed in the lining of a high-pressure reactor, and the oven temperature was set to 150 °C for a hydrothermal reaction for 14 h. The precursor was obtained by centrifugation and drying.
[0063] Weigh 0.3 g of the precursor and 1.5 mL of carbon disulfide and place them in a tube furnace. Evacuate the tube furnace to negative pressure and calcine at 1500 °C for 1 h to obtain SrTi(O) x S1-x 3.
[0064] Figure 1 SrTi(O) prepared for this invention x S 1-x The X-ray powder diffraction (XRD) pattern of the prepared product is shown in the figure. It can be seen from the figure that the diffraction peaks of the prepared product are similar to those of the standard card SrTiO3 (PDF#74-1296) and Sr... 1.15 The same as TiS3 (PDF#49-1367).
[0065] Figure 2 The X-ray powder diffraction (XRD) patterns of the synthesized strontium titanate, SrTi(OxS1-x)3, and strontium titanium sulfide prepared in this invention are shown in the figure. It can be seen from the figure that the diffraction peaks of the prepared products gradually change with the change of sulfur content.
[0066] like Figure 3 Strontium titanate and SrTi(O) are respectively. x S 1-x The scanning electron microscope (SEM) images of SrTi(OxS1-x)3 and SrTi(OxS1-x)3 show that SrTi(OxS1-x)3 has a nanocubic morphology, SrTi(OxS1-x)3 has a lamellar morphology, and SrTi(OxS1-x)3 has a structure in between, indicating that the incorporation of sulfur also affects the morphology of the catalyst.
[0067] It should be noted that the above description is only a part of the embodiments of the present invention, and all equivalent changes made to the system described in this invention are included within the protection scope of this invention. Those skilled in the art can make similar substitutions to the specific examples described, as long as they do not deviate from the structure of the invention or exceed the scope defined in these claims, all of which fall within the protection scope of this invention.
Claims
1. A method for preparing a bandgap tunable sulfur-oxygen-titanium-strontium catalyst, characterized in that, Includes the following steps: Step 1: After dissolving the strontium source and titanium source, add them to an alkaline solution, stir thoroughly, and carry out a hydrothermal reaction. After centrifugation and drying, the precursor is obtained. Step 2: Mix the precursor obtained in Step 1 with a sulfur source. The molar ratio of the precursor powder to the sulfur source is 1:8~20. The sulfur source is carbon disulfide that has undergone low-temperature pretreatment at a temperature below -10℃. Under negative pressure, the sulfur source is rapidly volatilized into gas and fills the calcination container. The calcination temperature is 500~1500℃, and the calcination time is 1~8 h, to obtain a band-tunable sulfur-oxygen-titanium-strontium catalyst. The band-tunable sulfur-oxygen-titanium-strontium catalyst is used for photocatalytic water splitting.
2. The method of claim 1, wherein the method is characterized by: In step 1, the strontium source is strontium chloride or strontium hydroxide, and the titanium source is tetrabutyl titanate or titanium isopropoxide. The molar ratio of strontium to titanium is 1:
1.
3. The method of claim 2, wherein the method is characterized by: The strontium source was dissolved in deionized water, and the titanium source was dissolved in anhydrous ethanol.
4. The method of claim 1, wherein the method is characterized by: In step 1, the hydrothermal reaction temperature is 80~200℃ and the time is 10~30h.
5. The method for preparing the bandgap tunable sulfur-oxygen-titanium-strontium catalyst according to claim 1, characterized in that, The hydrothermal reaction in step 1 is carried out in a high-pressure reactor, and the calcination in step 2 is carried out in a tubular furnace.
6. The bandgap tunable sulfur-oxygen-titanium-strontium catalyst prepared by the preparation method according to any one of claims 1 to 5, characterized in that, Its morphology is between that of nanocubes and lamellar structures.
7. The application of the bandgap tunable sulfur-oxygen-titanium-strontium catalyst according to claim 6 as a total water splitting photocatalyst.
Citation Information
Patent Citations
Method for preparing nanometer strontium titanate powder
CN105036184A
MXene-derived SrTiO3-based photocatalyst and application thereof
CN115582111A